PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN PADA INDUSTRI INFORMATION AND COMMUNICATIONS TECHNOLOGY DI INDONESIA - Tejasunarya, Jaka Laksana; Hanifah, Imam Abu (JURNAL RISET AKUNTANSI TIRTAYASA, 2018)
The purpose of this research is to find out the influence of intellectual capital which is proxy with the Pulic Model of Value Added Intellectual Coefficient (VAIC) through three components include Value Added Capital Employed (VACA), Value Added Human Capital (VAHU), Structural Capital Value Added (STVA) to the company financial performance that is proxy with the return on asset (ROA), Return on Equity (ROE), Return On Investments (ROI) on the company’s Information and Communications Technology (ICT) in Indonesian. The population is ICT companies which are listed in Indonesian Stock Exchange (IDX). The sample collection technique has bean determined by using purposive sampling and it is based on determined criteria therefore the samples are 15 ICT companies that publish financial statements for 6 consecutive years from 2010 to 2015. Multiple linier regressions with the SPSS application 2.1 versions are used in this research. The result of the research show that: 1) VACA, VAHU, STVA have been fix in predicting ROA, ROE, ROI. 2) VACA variable has significant influence to ROA, ROE, ROI in the positive direction. 3) VAHU variable has significant influence to ROA, ROE, ROI in the negative direction. 4) STVA variable has significant influence to ROA, ROE, ROI in the positive direction. Keywords: Intellectual Capital, Value Added Capital Employed, Value Added Human Capital, Structural Capital Value Added, Return On Assets, Return On Equity, Return On Investments.             The purpose of this research is to find out the influence of intellectual capital which is proxy with the Pulic Model of Value Added Intellectual Coefficient (VAIC) through three components include Value Added Capital Employed (VACA), Value Added Human Capital (VAHU), Structural Capital Value Added (STVA) to the company financial performance that is proxy with the return on asset (ROA), Return on Equity (ROE), Return On Investments (ROI) on the company’s Information and Communications Technology (ICT) in Indonesian. The population is ICT companies which are listed in Indonesian Stock Exchange (IDX). The sample collection technique has bean determined by using purposive sampling and it is based on determined criteria therefore the samples are 15 ICT companies that publish financial statements for 6 consecutive years from 2010 to 2015. Multiple linier regressions with the SPSS application 2.1 versions are used in this research. The result of the research show that: 1) VACA, VAHU, STVA have been fix in predicting ROA, ROE, ROI. 2) VACA variable has significant influence to ROA, ROE, ROI in the positive direction. 3) VAHU variable has significant influence to ROA, ROE, ROI in the negative direction. 4) STVA variable has significant influence to ROA, ROE, ROI in the positive direction.Keywords: Intellectual Capital, Value Added Capital Employed, Value Added Human Capital, Structural Capital Value Added, Return On Assets, Return On Equity, Return On Investments.